Treatment-Induced Anaemia in Hepatitis C Patients and Role of Erythropoietin in its Management - Nadim Iqbal Sheikh, Nadim Iqbal Sheikh; Anila Nisar, Anila Nisar; Shahzad Manzoor, Shahzad Manzoor; M. Shoaib Shafi, M. Shoaib Shafi; Shahid Abbasi, Shahid Abbasi; Bushra Kahoot, Bushra Kahoot; Iffat Sultana, Iffat Sultana (Journal of Rawalpindi Medical College, 2008)
Background: To study the incidence of anaemia during antiviral treatment and the effectiveness of erythropoietin to correct it. Methods: This prospective, observational study included 208 subjects with PCR positive for HCV RNA who presented in Shafi Clinic Rawalpindi. Duration of the study was 2 years. All patients were given antiviral treatment including interferon and ribavirin. Baseline Hb and all other laboratory parameters were checked. Any drop in Hb after initiation of therapy was noted. Patients who had Hb < 10g/dl were given inj erythropoietin for correction of anaemia. Results: Of the 208 patients, 99 were males (48%) and 107 (52%) females. 172 patients (82.7%) were given conventional interferon whereas 38 patients (17.3%) were given PEG-IFN along with ribavirin. Anaemia ie Hb less than 10g/dl developed in 38 cases (18.5%). Hb <8g/dl developed in 7 cases (3.4%). Out of these 38 cases; 30 patients had received conventional interferon whereas 8 patients had received PEG-IFN. Mean drop in Hb was from 11.5 to 6.0 g/dl mostly seen between 2-4 weeks. All patients were given inj Epo . All had significant increase in Hb upto 11.5 +/- 0.2 g/dl over 6-8 weeks. No patient required treatment discontinuation because of anaemia. Conclusion: It is concluded that anaemia is a common adverse effect of antiviral treatment. Recombinant human erythropoietin alpha is very effective to counter this problem without requiring blood transfusion or dose reduction. It allows adherence and maintenance of critical dose level producing optimal HCV treatment.